The association between exposure to aflatoxin, mutation in TP53,infection with hepatitis B virus, and occurrence of liver disease in a selected population in Hyderabad, India - Anitha, S.; Raghunadharao, D.; Waliyar, Farid; Sudini, H.; Parveen, M.; Rao, R.; Kumar, P. Lava (Elsevier, 2014)
Aflatoxin B1 is a carcinogen produced by Aspergillus flavus and a few related fungi that are often presentin many food substances. It interacts synergistically with Hepatitis B or C virus (HBV, HBC) infection,thereby increasing the risk of hepatocellular carcinoma (HCC). The G to T transversion at the third positionof codon 249 (AGG) of the TP53 gene, substituting arginine to serine, is the most common aflatoxininducedmutation linked to HCC. This study examined mutations in TP53 by PCR-RFLP analysis and bymeasurement of an aflatoxin-albumin adduct as a biomarker for human exposure of aflatoxin B1 byindirect-competitive ELISA, in samples collected from healthy controls as well as patients with hepatitisin Hyderabad, Andhra Pradesh, India. A total of 238 blood samples were analyzed the presence of the G toT mutation. Eighteen of these samples were from HBV-positive subjects, 112 of these were from subjectswho had HBV-induced liver cirrhosis, and 108 samples were taken from subjects without HBV infectionor liver cirrhosis (control group). The G to T mutation was detected in 10 samples, 8 of which werefrom subjects positive to both HBV and aflatoxin-albumin adduct in blood (p = 0.07); whilst two werefrom individuals who were HBV-negative, but positive for the aflatoxin-albumin adduct (p = 0.14). Theaflatoxin-albumin adduct was detected in 37 of 238 samples, 29 samples were from HBV-positive subjectsand eight were from individuals who were positive for both HBV and the TP53 mutation (p = 0.07). Theconcentration of aflatoxin-albumin adduct ranged from 2.5 to 667 pg/mg albumin. Despite low incidenceof the G to T mutation, its detection in subjects positive to aflatoxin-adducts is indicative of a strongassociation between the mutation and aflatoxin exposure in India.